2005
DOI: 10.1084/jem.20050693
|View full text |Cite
|
Sign up to set email alerts
|

Modifier loci condition autoimmunity provoked by Aire deficiency

Abstract: Loss of function mutations in the autoimmune regulator (Aire) gene in autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy patients and mutant mice lead to autoimmune manifestations that segregate as a monogenic trait, but with wide variation in the spectrum of organs targeted. To investigate the cause of this variability, the Aire knockout mutation was backcrossed to mice of diverse genetic backgrounds. The background loci strongly influenced the pattern of organs that were targeted (stomach, eye, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
245
4
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(278 citation statements)
references
References 50 publications
25
245
4
4
Order By: Relevance
“…2a), with a mean difference of 0.67 fg/pg 18S. As was previously established in recent literature [21,33,34], the AIRE transcription factor has a major role in the expression of the Ins2 gene in the thymus. Therefore, it was important to assess whether this decrease in the Ins2 mRNA was due to a decrease in the expression of Aire, which was also quantified by real-time PCR.…”
Section: Resultssupporting
confidence: 52%
“…2a), with a mean difference of 0.67 fg/pg 18S. As was previously established in recent literature [21,33,34], the AIRE transcription factor has a major role in the expression of the Ins2 gene in the thymus. Therefore, it was important to assess whether this decrease in the Ins2 mRNA was due to a decrease in the expression of Aire, which was also quantified by real-time PCR.…”
Section: Resultssupporting
confidence: 52%
“…This finding has a parallel in a recent study of NOD mice in which Treg cells were shown to participate in early insulitis and prevent the onset of T cell-mediated tissue destruction (32). Also, it has been suggested that the immunopathology developing in Aire Ϫ/Ϫ NOD mice might reflect the combined effect of failed central tolerance and defects of regulation intrinsic to the NOD strain (15), and a cross between Aire Ϫ/Ϫ and FoxP3 Ϫ/Ϫ mice proved rapidly lethal (19). It is tempting to speculate that the difference in Treg cell function and the participation of Treg cells in the murine tissue infiltrates might explain why Aire Ϫ/Ϫ mice remain clinically healthy while AIRE Ϫ/Ϫ humans invariably develop APECED.…”
Section: Discussionsupporting
confidence: 55%
“…However, in striking contrast to AIRE Ϫ/Ϫ humans who invariably develop clinical autoimmunity, the Aire Ϫ/Ϫ mice remain clinically healthy or in a few cases develop manifestations not seen in human APECED. These manifestations include an inflammation of lacrimal glands in one mouse strain (14) and inflammation of the exocrine pancreas in Aire Ϫ/Ϫ NOD mice (15). Simultaneous expression of an Ag targeted to pancreatic islets and a transgenic TCR specific to it triggers diabetes in Aire Ϫ/Ϫ mice, but thymic expression of the model Ag was shown to be Aire-independent (10).…”
mentioning
confidence: 99%
“…Furthermore, the number of endothelial cells in Aire -/-lungs was also increased. Jiang et al [57] recently reported that Aire -/-mice backcrossed in the NOD background die of pneumonitis. We have also observed lymphocytic infiltrates in the lungs of C57BL/6 Aire -/-mice (unpublished observation).…”
Section: Discussionmentioning
confidence: 99%